Influences of bacterial extracellular vesicles on macrophage immune functions - Jiang, Bowei; Huang, Junyun (Frontiers in Cellular and Infection Microbiology, 2024)
Bacterial extracellular vesicles (EVs) are crucial mediators of information transfer between bacteria and host cells. Macrophages, as key effector cells in the innate immune system, have garnered widespread attention for their interactions with bacterial EVs. Increasing evidence indicates that bacterial EVs can be internalized by macrophages through multiple pathways, thereby influencing their immune functions. These functions include inflammatory responses, antimicrobial activity, antigen presentation, and programmed cell death. Therefore, this review summarizes current research on the interactions between bacterial EVs and macrophages. This will aid in the deeper understanding of immune modulation mediated by pathogenic microorganisms and provide a basis for developing novel antibacterial therapeutic strategies.